2017
DOI: 10.1111/iwj.12767
|View full text |Cite
|
Sign up to set email alerts
|

The financial and quality‐of‐life cost to patients living with a chronic wound in the community

Abstract: Chronic wounds are associated with financial and personal costs. The system level expense associated with chronic wounds has been established, however, the out-of-pocket cost incurred by individuals who self-fund has not been the focus of extensive investigation. Recently, there has been renewed interest in evaluating quality of life, in line with the shift to patient enablement and self-care in chronic disease management. The objectives of this research were to describe the out-of-pocket wound treatment costs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 38 publications
4
71
0
3
Order By: Relevance
“…26 This study found that participants spent AU $2475.00 (2017 dollars), on average, on wound dressing products since the wound started (with an average wound duration of 109 weeks). 26 It also reported that people spent AU$121.82 on their wound in the most recent 28 days, which represented 10% of their disposable income. 26 Although this study was not specific to VLUs, it supports our finding that the cost of wound care is significant.…”
Section: Costsmentioning
confidence: 86%
See 2 more Smart Citations
“…26 This study found that participants spent AU $2475.00 (2017 dollars), on average, on wound dressing products since the wound started (with an average wound duration of 109 weeks). 26 It also reported that people spent AU$121.82 on their wound in the most recent 28 days, which represented 10% of their disposable income. 26 Although this study was not specific to VLUs, it supports our finding that the cost of wound care is significant.…”
Section: Costsmentioning
confidence: 86%
“…A third study measured costs for people living in the community, in Australia and Wales, with chronic wounds generally . This study found that participants spent AU$2475.00 (2017 dollars), on average, on wound dressing products since the wound started (with an average wound duration of 109 weeks) . It also reported that people spent AU$121.82 on their wound in the most recent 28 days, which represented 10% of their disposable income .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants reported a high level of self-efficacy (33⋅9/40) and moderate level of perceived social support (68/100) (Refer Tables 1 and 2). Further information about the characteristics of the sample, out-of-pocket wound treatment costs and quality of life has been previously reported (4). Results for the sample of 100 participants have been reported, unless otherwise specified.…”
Section: Screening Inclusion and Exclusionmentioning
confidence: 99%
“…Self‐treatment of chronic wounds involves wound cleansing, wound inspection, applying and removing wound dressings and/or applying and removing other therapies such as compression bandaging . How and why individuals self‐treat chronic wounds has not been systematically investigated, although this practice has been noted as preferable and acceptable in case study research and is reported to occur among individuals who have malignant wounds .…”
Section: Introductionmentioning
confidence: 99%